First Nations Voices in Child Protection Decision Making: Changing the Frame - Stubbs, Glendra; Rice, Elizabeth (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2023)
First Nations children in Australia remain vastly over-represented in the child protection (CP) and out-of-home care (OOHC) systems, and in juvenile detention and adult incarceration systems. To change this, we need to tackle the problem at the source; by maintaining our efforts for the implementation of First Nations rights, so that self-determination and cultural safety are embedded into the child protection system from a family’s first contact and by constantly identifying opportunities in the current system to keep our children safe. Using policy and research literature, this paper identifies the principal barrier to change as the continuing failure of settler governance to recognise the fundamental importance of First Nations rights, including the need to embed self-determination and a specific, First Nations cultural framework into the child protection system.The article also offers personal reflections on the essential role of self-determination in keeping our children safe, drawing on Aunty Glendra Stubbs’ experiences in community-based advocacy and support of families for nearly three decades. Her reflections are linked to the literature and First Nations advocacy that support the findings and opportunities for change proposed in this paper.